Instagram Antara Publish dan Privasi Bagi Generasi Z - Dhiya Aula Fillah; Cut Chusnul Agmeliani (Sadida Islamic Communications and Media Studies, 2025)
Generation Z lives in the midst of a paradox between the desire to showcase themselves publicly on Instagram and the awareness of the importance of privacy. This research explores the dilemma faced by Generation Z in using Instagram, namely the desire to publish content and the need to maintain privacy. Generation Z is caught in the dilemma between publishing and privacy. On one hand, they want to publish the content they create, but on the other hand, they want to maintain privacy over that content, yet unconsciously, they have shared private things. With a descriptive qualitative approach, this study uses the Self-Disclosure and Johari Window theories to analyze how Generation Z manages their digital identity. The research results show that Generation Z utilizes Instagram features such as private mode and close friends to balance openness and privacy. They selectively share information to build their self-image while maintaining control over their personal aspects. These findings provide insights into how social media can support young people in navigating between publicity and privacy, as well as its implications for digital identity management in the modern era.